Pengaruh Kepemimpinan Kepala Sekolah dan Budaya Organisasi terhadap Kinerja Guru - Rasyid Ridho Harahap; Remon Lapisa; Milana Milana; Delima Yanti Sari (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The aims of this research were (i) to find out the effect of the leadership of the principal on the performance of teachers at the 1 Sei Kanan State Vocational High School (ii) to find out the effect of organizational culture on the performance of teachers at the 1 Sei Kanan Public Vocational High School (iii) To simultaneously find out the effect of leadership school principals and organizational culture on teacher performance at State Vocational High School 1 Sei Right. The type of research used is quantitative and uses a descriptive approach. The method used in finding research results is by distributing questionnaires. The research results obtained are (1) Principal leadership has a good and significant influence on teacher performance by 34.2%. This indicates that the principal's leadership is getting better, so that the teacher's work is getting better. and vice versa. (2) Organizational culture has a good and significant effect on teacher performance by 34.6%. Based on these results, it shows that the better or better the organizational culture, the better and better the teacher's work and vice versa. (3) School leadership and organizational culture have a positive and significant effect on teacher effectiveness (51.1%). The better the leadership and organizational culture of the principal, the better the performance of the teacher. On the other hand, low or weakened leadership and organizational culture of school principals lead to poor teacher performance at SMKN 1 Sei Kanan Academic 2022/2023.